Practical Whole-System Persistence - Nguyen, Dustin Tien; Giersch, Oliver; Preisner, Thomas; Kapitza, Rüdiger; Krebs, Jonathan; Herzog, Henriette; Nolte, Jörg; Hönig, Timo; Schröder-Preikschat, Wolfgang (Proceedings of the 18th ACM International Systems and Storage Conference, SYSTOR 2025, 2025)
Sudden power outages remain one of the biggest threats to losing data, disrupting systems and causing financial damages. Whole system persistence (WSP) has previously been proposed as a solution to mitigate such threats through the use of non-volatile main memory (NVRAM). However, it missed out on external device state persistence and the NVRAM technology used at the time was expensive and limited with regard to their scalability. Today’s NVRAM technologies are both more affordable and offer much higher storage capacities, but are typically slower than DRAM. In this paper, we show how WSP can be attained for general-purpose operating systems using modern hardware. Unlike previous attempts at realising WSP, we discuss and evaluate practical solutions that allow us to also include external devices in our considerations for practical system-wide persistence (pWSP). Despite having the OS and all applications running in slower memory, we are able to show, that specific applications that otherwise have to rely on userspace persistence mechanisms, can achieve up to 2× better throughput and up to 1.5× reduced latency, as well as significantly lower latency variance in general. We further demonstrate, that power outage-related service downtime can be reduced from potentially hours down to just minutes, allowing even network connections to continue seamlessly in many cases.
CRIS-Team Scopus Importer:2025-10-16
Keywords: Operating System; Persistent Memory; Power failure